2005
DOI: 10.1136/thx.2004.037531
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxaemia enhances peripheral muscle oxidative stress in chronic obstructive pulmonary disease

Abstract: Background: Because oxidative stress affects muscle function, the underlying mechanism to explain exercise induced peripheral muscle oxidative stress in patients with chronic obstructive pulmonary disease (COPD) is clinically relevant. This study investigated whether chronic hypoxaemia in COPD worsens peripheral muscle oxidative stress and whether an abnormal muscle inflammatory process is associated with it. Methods: Nine chronically hypoxaemic and nine non-hypoxaemic patients performed repeated knee extensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
108
2
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(122 citation statements)
references
References 45 publications
8
108
2
3
Order By: Relevance
“…Jakobsson and colleagues (1990) have reported that adenosine triphosphate (ATP), glycogen and creatine phosphate levels in quadriceps muscle fi bers are signifi cantly reduced in COPD patients with chronic respiratory failure as compared to those without respiratory failure and they described a significant correlation between muscle metabolites and arterial PO 2 . Moreover, chronic hypoxemic COPD patients show greater levels of exercise-induced lipid peroxidation and oxidized proteins in their quadriceps muscles than do nonhypoxemic COPD patients (Koechlin et al 2005). As with the case of lower limb muscles, maximum diaphragm force and diaphragm endurance are both signifi cantly reduced in COPD patients with chronic hypoxemia, although inhalation of O 2 for 15min elicits an increase in diaphragm strength and endurance (Zattara-Hartmann et al 1995).…”
Section: Hypoxemiamentioning
confidence: 98%
“…Jakobsson and colleagues (1990) have reported that adenosine triphosphate (ATP), glycogen and creatine phosphate levels in quadriceps muscle fi bers are signifi cantly reduced in COPD patients with chronic respiratory failure as compared to those without respiratory failure and they described a significant correlation between muscle metabolites and arterial PO 2 . Moreover, chronic hypoxemic COPD patients show greater levels of exercise-induced lipid peroxidation and oxidized proteins in their quadriceps muscles than do nonhypoxemic COPD patients (Koechlin et al 2005). As with the case of lower limb muscles, maximum diaphragm force and diaphragm endurance are both signifi cantly reduced in COPD patients with chronic hypoxemia, although inhalation of O 2 for 15min elicits an increase in diaphragm strength and endurance (Zattara-Hartmann et al 1995).…”
Section: Hypoxemiamentioning
confidence: 98%
“…Activity or mobility in critically ill patients may initiate hypoxia; hypoxia is a source of increased oxidants [94,95]. Koechlin and colleagues [96] suggest that arterial oxygenation is key to reducing oxidative stress in patients who have COPD. In a sample of 10 subjects who had COPD, plasma levels of products of oxidative stress were increased significantly over similar products formed by seven controls at 6 hours after one episode of quadriceps endurance activity.…”
Section: Oxidants Cytokines and Activitymentioning
confidence: 99%
“…(4) However, the systemic effects of nocturnal hypoxemia have been little studied in patients with COPD.…”
Section: Introductionmentioning
confidence: 99%